Sustainable dynamic lot sizing models for cold products under carbon cap policy. (November 2020) - As'ad, Rami; Hariga, Moncer; Shamayleh, Abdulrahim
Highlights: A cold product exhibiting a discrete time varying demand is considered. Two models are presented one for the total carbon cap and the other for periodic cap. A lagrangean relaxation and a bi-section method based algorithms are developed for Model 1. Model 2 is solved via a dynamic programming based algorithm. Sensitivity analysis is performed on the effect of the preset total and periodic caps. Abstract: Amid the ever growing interest in operational supply chain models that incorporate environmental aspects as an integral part of the decision making process, this paper addresses the dynamic lot sizing problem of a cold product while accounting for carbon emissions generated during temperature-controlled storage and transportation activities. We present two mixed integer programming models to tackle the two cases where the carbon cap is imposed over the whole planning horizon versus the more stringent version of a cap per period. For the first model, a Lagrangian relaxation approach is proposed which provides a mean for comparing the operational cost and carbon footprint performance of the carbon tax and the carbon cap policies. Subsequently, a Bisection based algorithm is developed to solve the relaxed model and generate the optimal ordering policy. The second model, however, is solved via a dynamic programming based algorithm while respecting two established lower and upper bounds on the periodic carbon cap. The results of the computational experiments for the first model display a stepwise increase (decrease) in the total carbon emissions (operational cost) as the preset cap value is increased. A similar behavior is also observed for the second model with the exception that paradoxical increases in the total emissions are sometimes realized with slightly tighter values of the periodic cap.